Flatwise Compressive Properties of Kenaf/Polypropylene Honeycomb Core - Sallih, N. (Institute of Physics Publishing, 2018)
Light weight and sustainable sandwich panels are increasingly sought for an extensive range of applications, from structures in airliners to wall linings in buildings. A study on flatwise compressive properties of honeycomb cores manufactured from kenaf/polypropylene sheets has been conducted. The influences of directionalities, the thickness-to-length ratio of cell walls and the depth to cell size ratio on the stiffness and strength of the cores have been examined. Cell wall thickness, core depth, directionality, and the interaction between core depth and cell wall thickness influenced both absolute and specific compressive strengths of the cores. Directionality and cell wall thickness as well as interaction between cell wall thickness and core depth influenced the absolute compressive modulus of the cores. However, only directionality and interaction between cell wall thickness and core depth affected specific compressive modulus. Â© Published under licence by IOP Publishing Ltd.